Gestión educativa y necesidades de capacitación de los docentes del Instituto Tecnólogico Cordillera de la ciudad de Quito. Propuesta de un programa de capacitación andragógica para los docentes de la Institución. - Ortiz Yépez, Fernando Xavier (2013)
The beginning of this century globally has brought important changes, transcendental, in education. In the case of our country, also evidenced important changes, changes ranging from its legal basis, there are assessment processes that will allow accreditation of educational institutions, a situation that has caused a revolution in educational institutions, particularly in the higher level, and in almost all institutions concerned about accreditation, has led to significant and serious reflection, that have expressed interest in continuing to be better. As part of institutional concern, born the interest of having a program or teacher training system. This thesis, collecting this concern, start with a diagnosis of educational management of individual teachers, a situation that will effectively meet the training needs of community college faculty Cordillera of Quito, this institution in educational management of the city for more than thirty years and upgrade training of teachers, fundamental pillar of educational work, in which the leading role of teachers is revitalized by changing the levels of responsibility of learners. For the present research work with all teachers Institute Cordillera and students of final semester of the institution, considering that his criterion for diagnosis is the most qualified students who have already passed some semesters at the institution, who are graduating and whose assessment of teacher management of the institution, will be much more qualified than students of lower cycles. In the case of students will be a purposeful sample. The technique used is a survey for teachers with ten key items for teachers and another survey with ten questions for students will also be an interview with the three main authorities. The variables that will guide the research are: educational management and teacher training needs, for training proposal, will build a theoretical framework based on the characteristics of andragogical education and constructivism as educational management model. The beneficiaries of this research will be the students, teachers and school authorities directly and generally, the national education system. Terms: Education Management, teachers - TRAINING - constructivism, andragogy.